Studi Kegagalan Adhesi Granit Dinding di Masjid Al Wustha Marampiau Hilir: Study of Adhesion Failure of Granite Walls at Al Wustha Mosque, Marampiau Hilir - Aminullah, Aminullah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
The use of granite gives a majestic and authoritative impression to buildings of worship, and across generations. However, in many cases failures are found. This study highlights the failure of granite installation that occurred at Al Wustha Mosque, Margasari, a large mosque, and passed by the Hulu Sungai alternative road to Banjarmasin. Considering the high cost of granite work and the potential danger to the safety of the congregation, it is necessary to investigate the cause of the failure. This study explored academic sources, narration of events from witnesses (merbot), writings of practitioners' experiences, and knowledge products from granite-producing manufacturers. Data analysis was conducted by reconstructing the implementation method and comparing it with the theory of granite installation. It was found that some procedures were carried out properly, such as mixing adhesive paste, but there were also omissions, for example the implementer allegedly did not soak the granite before installation. In addition, there were shortcomings in the planning that did not anticipate the heat of the sun shining directly on the granite masonry. A number of recommendations are made in the conclusion of the study.